Comparative company law : text and cases on the laws governing corporations in Germany, the UK and the USA - Cahn, Andreas; Donald, David C., 1958- (Cambridge University Press, 2018)
When comparing the laws of different jurisdictions, one often sees only the forest or the trees. This is particularly problematic in comparative company law, where students hope both to understand the overall framework of the law and grasp its practical application. This text's structure, now in its second edition, solves that dilemma. Chapters open with discursive analyses of the law in each of Germany, the UK and the US (Delaware, the ABA Model Business Corporation Act, and federal securities laws) and set out the high-level governing framework, particularly for the EU and its member states. This analysis is succinct and pointed, with numerous references to both the law and leading scholarship. The whole text is arranged to highlight comparative aspects. Diagrams are used where helpful. Chapters close with edited judicial decisions from at least two of the jurisdictions discussed, which allows fresh exploration of comparison in more detail, and pointed questions to guide class discussion.